(untitled) (Modern education and development, 2025)
World literature is an integral part of human culture and history, expressing the thoughts, emotions, and life experiences of various peoples. It consists of a collection of works created worldwide and encompasses a rich diversity of literary genres, forms, and styles. Studying world literature enables individuals to better understand the cultures and traditions of other nations and broadens their worldview.